Nurturing Talent For Digital Transformation By Integrating Digital Upskilling With Career Pathing: A Case Study of A Company In Japan’s Energy Infrastructure Sector - Kazunori Kawai (International Journal of Science, Technology & Management, 2026)
This case study examines an intervention implemented by a company in Japan’s energy infrastructure sector to nurture digital talent. This intervention involved a digital upskilling program integrated with a career pathing program. The digital upskilling program delineated three categories of digital talent, corresponding to those in the Digital Transformation Promotion Skill Standard, and provided core courses for all employees along with category-specific courses. The career pathing program introduced the statuses of Digital Player and Digital Specialist, which employees could earn if they met the required conditions. Feedback on the intervention was obtained post-intervention through a questionnaire conducted among employees (n = 500, effective response rate of 95%) and interviews with ten employees who had gained the Digital Player status. The questionnaire responses revealed a difference between general and managerial staff in the level of interest in digital transformation and their ability to envisage applying digital technology in practice. The responses also suggested that the integrated intervention inspired younger employees to take initiative and encouraged a transformation in corporate culture. The case study provides a best-practice model for designing digital upskilling and career pathing programs in large, traditional companies in Japan.